Delusional infestation managed in a combined tropical medicine and psychiatry clinic. (20th September 2018) - Todd, Stacy; Squire, S Bertel; Bartlett, Robert; Lepping, Peter
Abstract: Background: Delusional infestation (DI) is a well-recognised delusional disorder presenting as the persisting belief in the presence of parasitic or other infestations. Combined clinics have been run by dermatology and psychiatry in a small number of centres. Here we report the first few years of a unique combined clinic run with experts in infectious diseases/tropical medicine and psychiatric management of DI. Methods: We reviewed all patients seen at the combined assessment clinics run at the Liverpool School of Tropical Medicine between 19 December 2011 and 31 October 2016. Data were collected prospectively as part of clinical assessment. Descriptive analysis of these data was performed to examine clinical features at assessment, investigations performed and treatment outcomes. Results: A total of 75 patients were assessed and 52 (69%) were given the formal diagnosis of DI. A history of travel was given by 64% of individuals but no significant tropical or infectious diagnosis was made. Of those who returned for follow-up, 61% reported improvement in symptoms. The Clinical Global Impressions Severity scale improvement was 1.36 for DI patients but only 0.63 for non-DI patients. DI patients were more impaired at baseline (5.0 vs 4.1). Health anxiety was the most common diagnosis seen in those not considered to have DI. Conclusions: Combined clinics to treat DI are effective in improving patient outcome. A significant minority of patients referred do not have a diagnosis of DI.